Breathing the Job: Impaired Pulmonary Function in Hairdressers due to Occupational Chemical Exposure - Demir Giden, Zeliha; Demir, Elif; Giden, Ramazan; Sevinç Akın, Hasret Yağmur (La Medicina del Lavoro, 2026)
Background: Hairdressers are occupationally exposed to harmful factors in the working environment and many cosmetic products. During the professional use of these products, there is exposure to many irritating, allergic, and carcinogenic chemicals, mainly through the skin and respiratory tract, and it is known that these occupational exposures are much more frequent and long-lasting than personal exposures. Hairdressing is one of the occupational groups with a high risk of respiratory diseases. In this study, we aimed to determine the extent to which the hairdressing profession affects respiratory functions. Methods: The present study included 50 people who had worked in hairdressing for at least three years, especially with hair products, had not been diagnosed with respiratory disease before this job, and did not smoke, and 50 healthy people with similar demographic characteristics. All respiratory complaints and sociodemographic information of the hairdressers were determined. Pulmonary function tests (PFTs) were performed on hairdressers and a healthy group, including FEV1, FVC, PEF, and FEV1/FVC ratio. Results: In the present study, we found that the hairdressing profession significantly increased the risk of respiratory symptoms. In addition, the increase in working hours as a hairdresser was associated with increased respiratory complaints, while hairdressers showed a statistically significant decrease in PFT values compared to the healthy group. Conclusions: Exclusion of smoking in our study reveals the occupational exposure more clearly. Our study provides additional evidence of a possible significant association between chemical exposure and increased respiratory symptom prevalence and decreased lung function.